Primordial Germ Cell Development in the Poeciliid, Gambusia holbrooki, Reveals Shared Features Between Lecithotrophs and Matrotrophs - Razmi, Komeil; Patil, Jawahar G. (Frontiers in Cell and Developmental Biology, 2022)
Metazoans exhibit two modes of PGC specification that are interspersed across taxa. However, the evolutionary link between the two modes and the reproductive strategies of lecithotrophy and matrotrophy is poorly understood. As a first step to understand this, the spatio-temporal expression of teleostean germ plasm markers was investigated in Gambusia holbrooki, a poecilid with shared lecitho- and matrotrophy. A group of germ plasm components was detected in the ovum suggesting maternal inheritance mode of PGC specification. However, the strictly zygotic activation of dnd-β and nanos1 occurred relatively early, reminiscent of models with induction mode (e.g., mice). The PGC clustering, migration and colonisation patterns shared resemblance to those of zebrafish, medaka and mice at blastula, gastrulation and somitogenesis respectively, recapitulating progressive adaptations from oviparity to matrotrophy. Similarly, the PGC markers shared expression domains that were unique to both teleost and murine models. Despite maternal acquisition of germ plasm, the collective pattern of PGC migration and spatial-temporal expression pattern of PGC markers were more similar to those of mammalian models, indicative of reproductive developmental adaptations consistent with the transition from lecithotrophy to one of matrotrophs.